Disinfection of dental impressions, disinfectant solutions and disinfection methods. Literature review - Arroyo Pérez, Carlos Alberto (2020)
Impression taking in dentistry is a frequent performed procedure and its contamination by microorganisms present in the oral flora requires that it be subjected to a disinfection procedure after being removed from the mouth, to minimize the risks of cross infection both in the clinic as in the laboratory. Impressions can be a source of infections transmission between the dentist and the laboratory due to the contact with saliva and blood of the patient, which then cross-infect the plaster casts. Several methods of impressions disinfection had been described in the literature that has their own advantages, disadvantages and effects on the impression material. In order to improve the knowledge and behavior of dental health workers regarding the disinfection of impressions, the present review summarizes current disinfection techniques as well as their effects on dimensional stability and reproduction of details of impression materials: The use of a mid-level disinfectant is recommended by the American Dental Association, chemical agents being more accessible than physical agents because of their easy application and lower cost. The most recommended disinfectant is 5.25% sodium hypochlorite, due to the minimal interactions with impression materials, although the solution is not very stable, it is economical and easy to obtain.